2020
DOI: 10.21037/jtd-20-871
|View full text |Cite
|
Sign up to set email alerts
|

Is total arch replacement associated with an increased risk after acute type A dissection?

Abstract: Background: The surgical strategy for acute type A aortic dissection (AADA) usually consists of reconstruction of the tear-lesion in the affected part of the ascending aorta. The optimal strategy either to replace the ascending aorta (AAR) or to replace the ascending aorta and the total aortic arch (TAAR) is still under debate. Our study compares the 30-day mortality between AAR and TAAR in AADA surgery. Methods: In this retrospective observational study, we analysed a total patient cohort of 339 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although being devoid of a statistical significance, total arch replacement was associated with high mortality in a German retrospective analysis. [5] Arch replacement had 23.8% mortality and ascending aorta replacement with a 16.8% and the propensity matching showed a lack of significance. Salem et al [5] reported 20.9% need for new-onset dialysis and 30.2% stroke rate postoperatively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although being devoid of a statistical significance, total arch replacement was associated with high mortality in a German retrospective analysis. [5] Arch replacement had 23.8% mortality and ascending aorta replacement with a 16.8% and the propensity matching showed a lack of significance. Salem et al [5] reported 20.9% need for new-onset dialysis and 30.2% stroke rate postoperatively.…”
Section: Discussionmentioning
confidence: 95%
“…[5] Arch replacement had 23.8% mortality and ascending aorta replacement with a 16.8% and the propensity matching showed a lack of significance. Salem et al [5] reported 20.9% need for new-onset dialysis and 30.2% stroke rate postoperatively. These rates are significantly higher than the rates of postoperative morbidity in our study.…”
Section: Discussionmentioning
confidence: 95%
“…(666)(667)(668) El reemplazo híbrido del arco con prótesis combinadas (trompa de elefante congelada) puede considerarse en casos de mala perfusión visceral y en casos de aneurisma o rotura torácica descendente (como pueden ser las disecciones retrógradas y la rotura intimal primaria en subclavia anómala). (669,670) El reemplazo extenso del arco en forma profiláctica puede considerarse en pacientes jóvenes, Marfan u otra aortopatía genética, ya que la tasa de complicaciones o reintervenciones relacionadas con la aorta en el seguimiento son elevadas y esto facilitaría un tratamiento posterior. (671-673)…”
Section: Manejo Quirúrgico De La Disección Tipo Aunclassified
“…The surgical technique and the protocol followed in our university hospital has been previously described [12]. Experienced senior surgeons performed all cases under general anesthesia with standard hemodynamic monitoring.…”
Section: Surgical Technique and Postoperative Managementmentioning
confidence: 99%